Canonical marital proceedings and Polish law - Pluta, Katarzyna (The Opole Studies in Administration and Law, 2019)
The article shows individual marital processes which can be carried out according to the norms of the Code of Canon Law. The author describes matrimonium non existens, nullity process, processus brevior, separation in marriage, a trial in case of the death of a spouse, matrimonium ratum et non consummatum, marriage dissolution in favorem fidei. The relationship between church courts and state courts in matrimonial matters is also described. The analyses included in the thesis show that regardless of the existence of many similarities, the described procedures are two different proceedings, whose aim was to describe interactions between spouses.